DAMPAK PENUTUPAN TEMPAT PEMBUANGAN AKHIR (TPA) BINUANG TERHADAP KELESTARIAN LINGKUNGAN DI KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR - Fadillah, Nur; Said, Muh; Sakmawati, Sakmawati (xxxx-xxxx, 2025)
This study aims to: 1) Describe the closure of the Binuang Final Disposal Site (TPA). 2) Analyze the impact of the closure of TPA Binuang on environmental sustainability in Wonomulyo District. 3) Identify solutions arising from the closure of TPA Binuang. The research used a qualitative descriptive method with the research location in Wonomulyo District. Data collection procedures included observation, interviews, and documentation. The data sources were primary and secondary data. Primary data were obtained from observations and interviews, while secondary data were obtained from documents, archives, and documentation. The results of this study indicate that: 1) The closure of the Binuang TPA was carried out based on a regional government decision in response to community demands and environmental considerations, so since December 21, the TPA has officially ceased operations. 2) The impact of the TPA Binuang closure on environmental sustainability in Wonomulyo District includes significant environmental pollution in the form of waste accumulation at various points disrupting community activities and damaging environmental aesthetics. Additionally, community resistance emerged due to the lack of effective waste management solutions. 3) Solutions resulting from the closure of TPA Binuang recommend collaboration between the government and the community to develop a sustainable waste management system to preserve the environment in Wonomulyo District, Polewali Mandar.